Analisis Pengelolaan Daycare yang Efektif Berdasarkan Kebutuhan dan Minat Anak di Daycare Bina Bangsa - Cucu Atikah; Siti Khosiah; Ayu Fajarwati (Universitas Islam Negeri Jurai Siwo Lampung, 2026)
The need for daycare services that can accommodate holistic child development is increasing along with the increasing number of working parents in the modern era. This study aims to analyze the management of Bina Bangsa Daycare, which applies a needs- and interests-based approach, and to assess the effectiveness of this management as a continuation of learning at Bina Bangsa Kindergarten/Kindergarten. The study used a qualitative approach using observation, in-depth interviews, and documentation techniques. The research subjects consisted of three early childhood education (PAUD) teachers directly involved in daycare management. Data analysis was conducted using the Miles and Huberman model, which includes data collection, data reduction, verification, and conclusion drawing. The results show that Bina Bangsa Daycare implements one structured activity each day, followed by free play activities that allow children to express their individual interests. This management is responsive to children's conditions after participating in centered learning at school, so that children receive a balance between cognitive, social, and emotional stimulation, as well as relaxation time. Teachers act as facilitators, adapting activities to children's needs and utilizing free play moments as a means of informal assessment. In addition, the continuity between centered learning at school and daycare activities creates a consistent and relevant learning experience for children. This study concludes that daycare management based on children's needs and interests has proven effective in supporting the holistic development of early childhood. However, challenges such as limited staffing and facilities require continuous improvement to ensure quality management.